Bubble pump: scalable strategy for in-plane liquid routing1. Issue 13 (7th July 2015) - Oskooei, Ali; Günther, Axel
<x xml:space="preserve">Abstract</x> We present an on-chip liquid routing technique intended for application in well-based microfluidic systems that require long-term active pumping at low to medium flowrates.